The “Cámara de Castilla” and Navarre - Ostolaza Elizondo, Isabel (Huarte de San Juan. Geografía e Historia, 2010)
The article studies the powers of the Cámara de Castilla as administrator of the royal faculties of pardon, mercy and ecclesiastic patronage in matters referring to Navarre. It also relates the role of the Viceroy, who, as the sovereign’s “alter ego”, had certain authority in these areas. From an archival perspective, guidelines are provided regarding the documentation affecting the kingdom, which was kept administratively separate from other territories belonging to the monarchy in the so-called books of Navarre. The books were kept in the General Archive of Simancas until the end of the XVI century and until the end of the Old Regime as far as the Secretariat of ecclesiastic patronage was concerned. And in the National Historical Archive in Madrid regarding the Secretariats of pardon and justice for the duration of the following centuries. It also makes reference to the sources contained in the viceroyal documentation and which are in the AGN. It should be pointed out that the specific status of Navarre was respected over the centuries, separating the management of Cámara matters from those of the other kingdoms under the monarchy.
Keywords: Cámara de Castilla and Navarre; Secretariats of pardon, mercy and ecclesiastic patronage